Revision of the genus Goniopsara Metcalf, 1952 (Hemiptera: Fulgoroidea: Nogodinidae), with the description of a new species from Laos - Gnezdilov, Vladimir M. (Zootaxa, 2024)
The nogodinid genus Goniopsara Metcalf, 1952 is revised. The type species of the genus, Goniopsara mystica (Melichar, 1899), is redescribed and illustrated along with male genitalia structure is examined and described for the first time. A new species, Goniopsara ridens sp. nov., is described from Laos. A key to species of Goniopsara is given and the relatioships of this genus with Goniopsarites Meng, Wang et Wang, 2014 is briefly discussed.